Hubungan tingkat kepuasan pasien terhadap kualitas pelayanan kefarmasian di apotek kabupaten badung : Patients satisfaction with pharmaceutical care in community pharmacies in the district of badung - wintariani, putu; Apsari, Dewi Puspita; Suwantara, I Putu Tangkas (Stikes Wira Medika Bali, 2021)
Pharmaceutical service is a direct and responsible service to patients related to pharmaceutical preparations with the aim of achieving definite results to improve the quality of life of the patient. Pharmacist interactions include providing information, monitoring drug use and knowing the final goal according to expectations to achieve patient satisfaction with pharmaceutical services. Patient satisfaction is the result of an assessment in the form of an emotional response (feeling happy and satisfied) because of the fulfillment of expectations or desires in using and receiving pharmaceutical services. This is a descriptive analytic study with a cross sectional survey design towards consumers who come to the pharmacy in Badung Regency, using a questionnaire as an instrument of data collection. The number of pharmacies that are willing to participate in this research is 15 pharmacies. Respondents in this study were pharmacy consumers, namely patients who received pharmaceutical services at the Badung district pharmacy and had met the inclusion-exclusion criteria. The results of the binary logistic test of patient characteristics stated that the level of customer satisfaction with the quality of pharmaceutical services at the Badung district pharmacy was not significant, including age (p = 0.761), gender (p = 0.612), education (p = 0.079), income level (p. = 0.139), occupation (p = 0.255), visit to the pharmacy (p = 0.392). Meanwhile, the pharmaceutical service category has a significant relationship with a value of 0,000 (p = 0,000) and has an effect of 11,495 times (or = 11,495). The statement of pharmaceutical services has a good and very good percentage which is indicated by statements such as pharmacists serving kindly (36.1%), treatment given according to consumer wishes (37.1%), and pharmacies having complete drugs and medical devices ( 38.1%).